PCET-Mediated Ring-Opening Alkenylation of Cycloalkanols via Dual Photoredox and Cobalt Catalysis - Ren, Zi-Gang; Yu, Wan-Lei; Zheng, Hai-Xue; Xu, Peng-Fei (Organic letters, 2023)
The construction of molecular skeletons and modification of molecules using widely available and easily prepared alcohols as radical precursors for coupling reactions are significant and challenging subjects. We herein report a straightforward strategy for the dehydrogenative ring-opening alkenylation of cycloalkanols with alkenes by combining a proton-coupled electron transfer strategy and a dual photoredox and cobalt catalysis system. With this approach, a series of distally unsaturated ketones were obtained in 17–83% yields with high E selectivity.